Collaboration and urban transport - Gonzalez-Feliu, Jesus; Pronello, Cristina; Salanova Grau, Josep Maria; Skačkauskas, Paulius (Transport, 2018)
With the development of innovative technologies for smart cities, sharing economy and collaborative practices, sharing and collaboration have become a major issue in urban transport. However, a common view about such concepts is still missing. The issue proposes a forum to present the latest development in the field and also to address the main challenging topics of research regarding collaborative urban transport. The Special Issue on Collaboration and Urban Transport includes 18 papers and is divided into two sections (papers No. 1–9 and No. 10–17 respectively, paper No. 18 – summarizing review paper). The first section is dealing with the research questions directly related to collaboration while the second section refers to jobs dealing with urban transport; the links to collaborations are indirect but have a potential.